THE INFLUENCE OF THE DISCIPLINE OF GENERAL ADMINISTRATION EMPLOYEES ON THE EFFECTIVENESS OF SERVICES AT THE LIMBOTO DUNDA HOSPITAL, GORONTALO CITY - Titin Dunggio; Lika Anggraini; Sarifudin Mada (Jurnal Ilmiah dr. Aloei Saboe, 2024)
Work discipline is a tool that managers use to communicate with employees so that they are willing to increase one's awareness of complying with all applicable regulations and social norms. Problem limitation is limiting the problem only in terms of timeliness or orderliness in managing administration. The formulation of the problem is the influence of discipline of general administration employees on the effectiveness of services at Dunda Limboto Regional Hospital. The aim of this research is to determine the influence of discipline of general administration employees on the effectiveness of services at Dunda Limboto Hospital. The research method used is correlational research. The sample in this study consisted of 18 respondents. Data analysis uses simple linear regression. The results of the research show that there is an influence of employee discipline on the effectiveness of services at Dunda Limboto Hospital. In conclusion, to improve employee work discipline and effectiveness, it is recommended to pay more attention to services and also to support effectiveness, you must also pay attention to the structure or facilities and infrastructure used. Work discipline is a tool that managers use to communicate with employees so that they are willing to increase one's awareness of complying with all applicable regulations and social norms. Problem limitation is limiting the problem only in terms of timeliness or orderliness in managing administration. The formulation of the problem is the influence of discipline of general administration employees on the effectiveness of services at Dunda Limboto Regional Hospital. The aim of this research is to determine the influence of discipline of general administration employees on the effectiveness of services at Dunda Limboto Hospital. The research method used is correlational research. The sample in this study consisted of 18 respondents. Data analysis uses simple linear regression. The results of the research show that there is an influence of employee discipline on the effectiveness of services at Dunda Limboto Hospital. In conclusion, to improve employee work discipline and effectiveness, it is recommended to pay more attention to services and also to support effectiveness, you must also pay attention to the structure or facilities and infrastructure used.